Assessing the effect of dialogue on altruism toward future generations: A preliminary study - Maalouly, Elie; Yamazaki, Ryuji; Nishio, Shuichi; Nørskov, Marco; Kamaga, Kohei; Komai, Shoji; Chiba, Kiyoshi; Atsumi, Keiichiro; Akao, Ken-Ichi (Frontiers in Computer Science, 2023)
Despite the abundance of evidence on climate change and its consequences on future generations, people, in general, are still reluctant to change their actions and behaviors towards the environment that would particularly benefit posterity. In this study, we took a preliminary step in a new research direction to explore humans’ altruistic behavior towards future generations of people and whether it can be affected by dialogue. We used an android robot called Telenoid as a representative of future generations by explaining that the robot is controlled by an Artificial Intelligence (AI) living in a simulation of our world in the future. To measure people's altruistic behavior towards it, we asked the participants to play a round of the Dictator Game with the Telenoid before having an interactive conversation with the Telenoid and then playing another round. On average, participants gave more money to the Telenoid in the second round (after having an interactive conversation). The average amount of money increased from 20% in the first to about 30% in the second round. The results indicate that the conversation with the robot might have been responsible for the change in altruistic behavior toward the Telenoid. Contrary to our expectations, the personality of the participants did not appear to have an influence on their change of behavior, but other factors might have contributed. We finally discuss the influence of other possible factors such as empathy and the appearance of the robot. However, the preliminary nature of this study should deter us from making any definitive conclusions, but the results are promising for establishing the ground for future experiments.